Comparison of pressurized liquid extraction with soxhlet extraction in the determination of polycyclic aromatic hydrocarbons in soil - Md. Saleh, Noorashikin (Malaysian Society of Analytical Sciences, 2009)
Pressurized liquid extraction (PLE) method was developed by using conventional high performance liquid chromatography instrument and the performance of the PLE system was tested using environmental soil samples were collected at different places from FELDA palm oil plantation at Serting, Negeri Sembilan. PLE method showed good reproducibility for the majority of PAHs tested. Fluoranthene showed the highest recovery (94.4%) followed by fluorene (92.3%), phenanthrene (88.5%) and naphthalene (81.5%). High temperature at 180°C along with polar solvent dichloromethane-acetone was found to be necessary to extract the PAHs quantitatively from soils. The PAHs detected in the samples are phenanthrene (4.1 to 49.4 µg/mL), fluorene (10.1 µg/mL and 11.6 µg/mL) and fluoranthene (2.2-60.7 µg/mL. Naphthalene was not detected in the soil samples. The results obtained indicate that the developed method can be applied to the analysis of PAHs in soils.